Sweetpotato slip planting density and slip length optimization for mass production of quality planting material in smallholder farm settings. - Kakuhenzire, R.; Mwenda, M.; Grant, F.; Kalaye, J. (2017)
Sweetpotato production in unimodal rainfall farming systems in sub-Saharan Africa is constrained by inadequate quality planting material. Technologies for efficient production of sweetpotato planting material are imperative to improve this sub-sector. Consequently, two separate field experiments, using five orange-fleshed sweetpotato varieties were conducted to determine the optimum slip spacing and slip length for optimal vine growth and vine-cutting production as planting material. Slip spacing levels were (15x15), (20x20), (25x25) and (30x30) cm. The slip length treatments were; 15, 20, 25 and 30 cm all planted at 20x20 cm spacing. The experimental sites were ARI Uyole, Mbeya in 2016 and 2017 and SUA, Morogoro only in 2017. Both experiments were set in split-split plots in randomized complete blocks with three replications. The vine growth rate (cm day<sup(-1)>) and vine-cutting yield m<sup(-2)> were significantly (P=0.05) higher at Morogoro than at Uyole. Cultivars; Kakamega and Ejumula, respectively had significantly (P=0.05) higher vine-cutting yield than Kiegea and Mataya while cultivar Kabode had intermediate yield. Vine-cutting yield was significantly (P=0.05) higher at (15x15) cm than at (30x30) and increased with repeated vine harvesting. The effect of slip length though significant (P=0.05) over varieties, years and locations was inconsistent except for fresh foliage yield (t ha<sup(-1)>).